Putting Global Education Through Transcript Based Lesson Analysis in Higher Education - Mutiani, Mutiani; Disman, Disman; Abbas, Ersis Warmansyah; Wiyanarti, Erlina; Hadi, Sutarto (FKIP Universitas Lampung, 2022)
Putting Global Education Through Transcript Based Lesson Analyes (TBLA) in Higher Education. Objectives: this research is to analyze conversations related to corruption and poverty. The two themes are: This research describes global educational practices that focus on achieving a global perspective in Transdisciplinary and Cross-Discipline Approaches in Social Studies Learning. Methods: This study uses a qualitative method as a research approach. The research was conducted from September 26 to October 10, 2021. Miles and Huberman's interactive model reduces interview data, presents research results in a descriptive narrative manner, and concludes research results. Findings: describing the differences in conversations that occurred in cycle one and cycle two, which the lecturer understood because students were reluctant to speak. The reluctance to express opinions is due to limited mastery of the material and fear of interpretation. Therefore, based on cycle one, the lecturer provides brainstorming by conveying the importance of expressing opinions in learning. Conclusion: of the study refers to the comparison of data in cycles one and two. Lecturers have the main role to provide brainstorming by conveying the importance of expressing opinions. In addition, the subject of transdisciplinary and interdisciplinary approaches in social studies learning puts forward the principles of scientific culture in the academic field. Keywords: global education, transcript-based lesson analyzes (TBLA), conversation.DOI: http://dx.doi.org/10.23960/jpp.v12.i2.202244